Pathophysiologic Implications of Reduced Podocyte Number in a Rat Model of Progressive Glomerular Injury - Macconi, Daniela (American Society for Investigative Pathology, 2006)
Changes in podocyte number or density have been suggested to play an important role in renal disease progression. Here, we investigated the temporal relationship between glomerular podocyte number and development of proteinuria and glomerulosclerosis in the male Munich Wistar Fromter (MWF) rat. We also assessed whether changes in podocyte number affect podocyte function and focused specifically on the slit diaphragm-associated protein nephrin. Age-matched Wistar rats were used as controls. Estimation of podocyte number per glomerulus was determined by digital morphometry of WT1-positive cells. MWF rats developed moderate hypertension, massive proteinuria, and glomerulosclerosis with age. Glomerular hypertrophy was already observed at 10 weeks of age and progressively increased thereafter. By contrast, mean podocyte number per glomerulus was lower than normal in young animals and further decreased with time. As a consequence, the capillary tuft volume per podocyte was more than threefold increased in older rats. Electron microscopy showed important changes in podocyte structure of MWF rats, with expansion of podocyte bodies surrounding glomerular filtration membrane. Glomerular nephrin expression was markedly altered in MWF rats and inversely correlated with both podocyte loss and proteinuria. Our findings suggest that reduction in podocyte number is an important determinant of podocyte dysfunction and progressive impairment of the glomerular permselectivity that lead to the development of massive proteinuria and ultimately to renal scarring.